Comparison of rapid versus slow maxillary expansion on patient-reported outcome measures in growing patients: a systematic review and meta-analysis - Valentina Rutili; Michele Nieri; Debora Franceschi; Felicita Pierleoni; Veronica Giuntini; Lorenzo Franchi (SpringerOpen, 2022)
Abstract Background No systematic review and meta-analysis are present in the literature comparing patient-reported outcome measures (PROMs) in rapid maxillary expansion (RME) versus slow maxillary expansion (SME) in growing patients. Objective The objective of this systematic review was to compare PROMs in RME versus SME in growing patients. Materials and Methods Electronic search in PubMed (MEDLINE), Cochrane Library, Scopus, Embase, Web of Science, and OpenGrey was conducted. Only RCTs were included. Inclusion criteria were: growing patients in the mixed dentition or early permanent dentition, mild-to-moderate maxillary transverse deficiency, dental crowding, treatment with fixed expanders for rapid and slow maxillary expansion. Risk of bias was assessed using RoB 2. GRADE statement was performed. The mean of the differences (MD) and the risk ratio (RR) were used for the aggregation of data. A random effect model was applied. Results Two articles with a total of 157 patients were finally included in the systematic review and meta-analysis. One article was at low risk of bias, while one was at risk of bias with some concerns. Pain presence was less, though not statistically significant, in SME patients (RR = 2.02, 95%CI from 0.55 to 7.49, P = 0.29, I 2 = 95%, 2 studies, GRADE very low). Pain intensity was significantly lower in SME appliance in the first week of treatment (pooled MD = 0.86 favoring SME, 95%CI from 0.47 to 1.26, P < 0.0001, I 2 = 6%, 2 studies, GRADE moderate). There were no significant differences between the two groups in difficulty in speaking, difficulty in swallowing, hypersalivation, difficulty in hygiene, and patient and parent satisfaction. Conclusions Pain intensity was significantly lower in SME compared to RME during the first week of treatment. For the following weeks, there were no differences in pain between the two protocols.